Anti-virulence activity of polyphenolic fraction isolated from Kombucha against Vibrio cholerae. (March 2020) - Bhattacharya, Debanjana; Sinha, Ritam; Mukherjee, Priyadarshini; Howlader, Debaki Ranjan; Nag, Dhrubajyoti; Sarkar, Soumyadev; Koley, Hemanta; Withey, Jeffrey H.; Gachhui, Ratan
Abstract: The use of traditional foods and beverages or their bioactive compounds as anti-virulence agents is a new alternative method to overcome the increased global emergence of antimicrobial resistance in enteric pathogens. In the present study, we investigated the anti-virulence activity of a polyphenolic fraction previously isolated from Kombucha, a 14-day fermented beverage of sugared black tea, against Vibrio cholerae O1. The isolated fraction was mainly composed of the polyphenols catechin and isorhamnetin. The fraction, the individual polyphenols and the combination of the individual polyphenols significantly inhibited bacterial swarming motility and expression of flagellar regulatory genes motY and flaC, even at sub-inhibitory concentrations. The polyphenolic compounds also decreased bacterial protease secretion and mucin penetration in vitro. In vivo study revealed that the polyphenolic fraction significantly inhibited V. cholerae induced fluid accumulation in the rabbit ileal loop model and intestinal colonization in suckling mice model. Therefore, the anti-virulence activity of the Kombucha polyphenolic fraction involved inhibition of motility and protease secretion of V. cholerae, thus preventing bacterial penetration through the mucin layer as well as fluid accumulation and bacterial colonization in the intestinal epithelial cells. The overall results implied that Kombucha might be considered as a potential alternative source of anti-virulence polyphenols against V. cholerae . To the best of our knowledge, this is the first report on the anti-virulence activity of Kombucha, mostly attributed to its polyphenolic content. Highlights: Kombucha polyphenolic fraction consisted of mainly catechin and isorhamnetin. Polyphenolic fraction showed anti-virulence activity against V. cholerae C6706. It inhibited bacterial motility, protease activity and mucin penetration in vitro. It inhibited bacteria-induced fluid accumulation in rabbit ileal loop model. It inhibited intestinal colonization in suckling mice model.